An Empirical Study on the Impact of Augmented Reality on Students' Learning Outcomes in Teaching Product Creative Design Courses - Lu, Wei; Zhu, Lu (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Augmented reality is one of the fastest developing technologies and more and more teachers are using AR to assist teaching and learning, this study aims to compare student learning outcomes of augmented reality and traditional instruction in teaching product creative design. Investigate the impact of augmented reality on learning outcomes by examining 74 students at a university in Guangdong Province, China. The learning outcomes of augmented reality teaching were compared with traditional teaching in terms of content knowledge, design process, and design outcomes through a product creative design course. Materials and Methods: A total of 74 university students participated in this study. The participants were divided into two groups: a control group and an experimental group. The control group was taught using traditional teaching methods and the experimental group was taught using augmented reality. At the end of an 8-week product creativity design course, the course was evaluated using a course evaluation scale that has been used by the college for many years. This assessment explored the outcomes of content knowledge, design process, and design outcomes. Results: Before the start of the course, a pre-test was administered to both groups of students using the Course Assessment Scale, which indicated that both groups had the same level of academic proficiency. At the end of the course, a post-test using the Course Assessment Scale revealed that the experimental group outperformed the control group in terms of content knowledge, design process, and design outcomes. Conclusion: The results of the study show that the use of augmented reality technology in a creative product design course has a positive impact on students' learning outcomes. By comparing the before and after side difference analysis of content knowledge, design process, and design outcome scores of the control and experimental groups, the study found that augmented reality technology helps to enhance students' learning outcomes.